Implementasi Kurikulum Pembinaan Pendidikan Agama Islam di Rumah Tahanan Negara Kelas IIB Salatiga - Noor Malihah; Agus Wijayanto (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2018)
The purpose of this research is to find out: 1). the implementation of curriculum in nurturing Islamic Education in the House of Detention IIB Salatiga. 2). the management of Islamic Education in the House of Detention IIB Salatiga prison. This research is a qualitative research and is a field research using a case study approach. The objects of this research are the head of the House of Detention, the inmates of the House of Detention IIB Salatiga, the officers of the House of Detention IIB Salatiga, the relevant documents used in House of Detention IIB Salatiga. The data are collected based on: interviews, documentation and data triangulation. The results of this research demonstrate that: the implementation of curriculum in nurturing Islamic Education for inmates in the House of Detention IIB Salatiga are based on a specific curriculum used a guide for Islamic spiritual advisers in the house of detention. The curriculum has been implemented properly so that the prisoner’s mental revolution program can be achieved, though not all. Efforts to revolutionize the mentality and change the character of prisoners are conducted intensively and continously through lectures, discussions and counseling guidance and advice to the inmates. Coaching methods are carried out in two ways, namely inside and outside the room